Politics of Anies Baswedan in the Presidential Candidate Video Bicara Gagasan: Study of Persuasive Messages - Nurdin, Hanifah; Samosir, Hasrat Efendi; ., Katimin (KOMUNIKA, 2023)
As the 2024 presidential election approaches, political campaigning is beginning in the Republic of Indonesia. One candidate who has not escaped the spotlight is Anies Rasyid Baswedan. In attracting sympathisers, Anies Rasyid Baswedan makes use of conventional and social media in campaigning. This study uses semiotic analysis to analyse the persuasive messages used by Anies in campaigning. In the Bacapres Bicara Gagasan event on the Narasinewsroom Youtube channel, Anies Rasyid Baswedan used persuasive messaging techniques. The message preparation techniques are fear appeal, emotional appeal, reward appeal, motivational appeal and humorous appeal. The research method used is qualitative text media analysis approach Charles Sanders Pierce. Where this method is known as the triadic method, representamen, object and interpretant. The results showed that Anies Baswedan at the Bacapres Bicara Gagasan event fulfilled the technique of preparing persuasive messages. The five message preparation techniques studied, Anies Rasyid Baswedan used all techniques in delivering messages in front of the audience. In addition, Anies Baswedan provides hopes and promises in the form of justice for the condition of Indonesia today.